2012
DOI: 10.1037/a0026709
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and cost-effectiveness of military telehealth mental health screening.

Abstract: Telehealth has been touted as one solution to the shortage of mental health providers within the military. Despite developing evidence for the equivalence of telehealth mental health care, there is no research that covers the use of telehealth for population mental health screening, a standard component of postdeployment medical screening. This paper summarizes soldier perceptions of three separate screening events in which telehealth was used and the cost-effectiveness of telehealth versus in-person implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…A study investigating telehealth mental health screening with military populations post-deployment found that using telehealth to screen large numbers of Veterans was more expensive than in-person screening. 42 Given the current lack of studies addressing the cost-effectiveness of telemedicine and discrepancies in the findings in this area of research, future investigations of the cost of this delivery modality are warranted.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…A study investigating telehealth mental health screening with military populations post-deployment found that using telehealth to screen large numbers of Veterans was more expensive than in-person screening. 42 Given the current lack of studies addressing the cost-effectiveness of telemedicine and discrepancies in the findings in this area of research, future investigations of the cost of this delivery modality are warranted.…”
mentioning
confidence: 98%
“…43 Furthermore, providing services via telemedicine requires additional training, administrative support, and technological expenses beyond those necessary for traditional clinical care. 42 In the future, payers, providers, and policy makers need to work together in order for telehealth to be adopted by a larger number of health service providers. 44 The current study represents a retrospective analysis of data from a randomized controlled trial that demonstrated non-inferiority of clinical effectiveness and comparable process outcomes for a groupadministered cognitive behavioral treatment for anger management delivered via CVT compared with in-person delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies compared the costs of different treatments and therapies for PTSD-afflicted individuals, especially compared to usual treatments of PTSD (psycho-and pharmacotherapy). [72][73][74][75][76] Regarding the small selection of studies in aggregate, it is apparent that the costs of different treatments vary widely.…”
Section: Program-evaluation Literaturementioning
confidence: 99%
“…'7 DoD telemedicine programs have also been dedicated to mental health,58 although cost savings and effectiveness are still being evaluated. 59 The VA has also extensively imple mented telemedicine programs,60 including those for mental health.61,62 Implementation of telehealth has enabled the development of mHealth approaches in the Military Health Service (MHS).63,64 Second in importance to command sup port is the identification of local clinical champions who will support the adoption and sustainment of mHealth initiatives.…”
Section: Command Policymentioning
confidence: 99%